Contrasting strategies used by lichen microalgae to cope with desiccation-rehydration stress revealed by metabolite profiling and cell wall analysis - Centeno, Danilo C.; Hell, Aline F.; Braga, Marcia R.; del Campo, Eva M.; Casano, Leonardo M. (Environmental microbiology, 2016)
Summary Most lichens in general, and their phycobionts in particular, are desiccation tolerant, but their mechanisms of desiccation tolerance (DT) remain obscure. The physiological responses and cell wall features of two putatively contrasting lichen‐forming microalgae, Trebouxia sp. TR9 (TR9), isolated from Ramalina farinacea (adapted to frequent desiccation‐rehydration cycles), and Coccomyxa solorina‐saccatae (Csol), obtained from Solorina saccata (growing in usually humid limestone crevices, subjected to seasonal dry periods) was characterized. Microalgal cultures were desiccated under 25%–30% RH and then rehydrated. Under these conditions, RWC and ψw decreased faster and simultaneously during dehydration in Csol, whereas TR9 maintained its ψw until 70% RWC. The metabolic profile indicated that polyols played a key role in DT of both microalgae. However, TR9 constitutively accumulated higher amounts of polyols, whereas Csol induced the polyol synthesis under desiccation–rehydration. Csol also accumulated ascorbic acid, while TR9 synthesized protective raffinose‐family oligosaccharides (RFOs) and increased its content of phenolics. Additionally, TR9 exhibited thicker and qualitatively different cell wall and extracellular polymeric layer compared with Csol, indicating higher water retention capability. The findings were consistent with the notion that lichen microalgae would have evolved distinct strategies to cope with desiccation–rehydration stress in correspondence with the water regime of their respective habitats.